Whole-body vibration promotes lipid mobilization in hypothalamic obesity rat. (February 2021) - de Andrade, Bárbara Zanardini; Zazula, Matheus Felipe; Bittencourt Guimarães, Ana Tereza; Sagae Schneider, Sara Cristina; Boaretto, Mariana Laís; Felicio Poncio, Ana Claudia; Hoff Nunes Maciel, Jhyslayne Ignacia; de Oliveira, Camila Maria Toigo; Costa, Rose Meire; Flor Bertolini, Gladson Ricardo; Chasko Ribeiro, Lucinéia de Fátima
Highlights: Physical exercise has been widely used to improving morbidities present in obese individuals. Whole-body vibration (WBV) therapy can help improve the lipid profile. WBV positively implying health and quality of life and rehabilitation in obese and pre-diabetic patients. Abstract: Objectives: This study aimed to analyze the effect of whole-body vibration (WBV) on metabolic parameters using the monosodium l -glutamate (MSG) model of obesity. Method: MSG-obese rats that were exposed to WBV on a vibrating platform with 60 Hz frequency, 2 mm amplitude, three times/week, 10 min/day, during eight weeks (from postnatal day (PN) 80 to PN136). Blood glucose, creatine kinases (CK and CK-MB) and lipid profile through plasma and liver levels of lipids and lipoproteins were evaluated. Morphology and oxidative stress of adipose and hepatic tissues were further evaluated. Results: When performing a WBV exercise, animals showed contrasting metabolic responses. Vibration Control group (CTL-WBV) presented a reduction in CK and liver triacylglycerol, an increase in glucose, lactate, total cholesterol, liver cholesterol, and LDL while MSG Vibration group (MSG-WBV) showed an increase in total triacylglycerol, VLDL, lactate, CK, liver cholesterol, additional liver lipid peroxidation and LDL, total cholesterol and CKMB reduction. Conclusion: Even although the MSG is a model of impacting injury, the metabolic demand of WBV exercise was able to induce mobilization of substrates, highlighting the lipid mobilization in obese animals, it should be used as a metabolic rehabilitation tool in patients with metabolic diseases, such as obesity and diabetes.